Building a Greener Future: How Earth Blocks Are Reshaping Sustainability and Circular Economy in Construction - Swati Sinha; Jayaraman Sethuraman Sudarsan (Architecture, 2025)
Sustainability has become an important focus in the construction industry due to growing environmental concerns, resource depletion, and the urgency to reduce greenhouse gas emissions. The construction sector contributes significantly to the world’s carbon emissions and energy consumption, making it a prime candidate for sustainable transformation. In response to these challenges, there has been a shift towards utilizing earth-based products, especially earth blocks, as sustainable alternatives. Compressed stabilized earth blocks (CSEBs) are garnering increased attention because of their ability to lower environmental impact. These blocks are made from locally sourced materials, reducing the transportation-related emissions and energy use. Their production processes typically require far less energy than traditional building blocks, which results in reduced carbon footprints. Earth blocks also contribute to sustainability through their thermal performance, which can enhance energy efficiency in buildings by naturally regulating indoor temperatures. As a result, less artificial heating and cooling is required, leading to further energy savings. Furthermore, CSEBs and other earth blocks can incorporate waste materials promoting a circular economy and resource efficiency. This paper explores the multifaceted role of earth blocks in sustainable construction by conducting a comprehensive systematic and bibliometric analysis. By evaluating research trends, the evolution of the field, and the broader impact of these materials, this study aims to provide a deeper understanding of the contributions of earth blocks to sustainability. Key areas of focus include identifying prominent research themes, emerging technologies, and future opportunities for incorporating earth blocks into mainstream construction practices. This approach aligns with the vision of advancing sustainable architecture and green buildings to minimize environmental pollution and resource consumption while supporting the transition to a circular economy in the built environment.